Pembuatan Media Promosi Video Konten Menggunakan Aplikasi Capcut di Tiktok untuk Meningkatkan Brand Awareness Pelumas PT Pertamina Lubricants Kota Malang - Delvia Imayuri Rudianto; Umi Khabibah; Heru Utomo (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This research aims to evaluate the effectiveness of using video content on TikTok as a digital promotional media to increase brand awareness of Enduro and Fastron lubricant products from PT Pertamina Lubricants in Malang City. Previously, promotions in this region relied on conventional media like banners which were less optimal in reaching wide consumers. Through the Kemmis and Taggart action research cycle approach, two promotional videos were produced utilizing the CapCut application and uploaded to TikTok. Data collection involved observation, interviews, and questionnaires distributed to fifteen respondents per video using purposive sampling techniques. Quantitative data analysis was conducted to measure effectiveness using the EPIC Model alongside the Guttman scale for brand awareness dimensions. The research results indicate that both promotional videos are categorized as highly effective based on Empathy, Persuasion, Impact, and Communication dimensions. Furthermore, measurements utilizing the Guttman scale prove that all brand awareness aspects, including brand recall, brand recognition, brand choice, and top of mind, gained excellent results. In conclusion, utilizing video content on the TikTok platform is a highly crucial and effective digital marketing strategy to expand overall audience reach. This significantly elevates consumer brand awareness towards superior PT Pertamina Lubricants products, ultimately attracting broader market segments.